Time Delay Compensation for the Superheated Steam Temperature Control System Based on a Practical Feedforward Gain-Scheduling Cascade Control Design with Stability Analysis - Tahereh Gholaminejad; Fereshteh Dadkhah-Tehrani; Mohsen Maboodi (MSD Institute, 2025)
Controlling the temperature of superheated steam (SST) is essential for the safe and efficient operation of combined cycle power plants, but it has become challenging due to frequent load variations and safety requirements. Traditional PI controllers may struggle to provide optimal performance because of non-linearity, time delays, and disturbances, particularly under wide-range load conditions. This paper proposes a new feedforward gain-scheduling cascade control strategy that compensates for time delays while ensuring stable SST without complicating the control system. The method incorporates a well-defined feedforward control mechanism into a gain-scheduling PI structure, enabling quick adjustments of the water spray control valve to prevent SST overshoots during sudden power fluctuations. A stability analysis is included, and the proposed strategy has been successfully simulated and implemented at two real combined cycle power plants in Iran, demonstrating its effectiveness in maintaining smooth temperature control and enhancing power output without adding complexity to the system.